(untitled) (Research, Society and Development, 2024)
Objective: To analyze the pandemic period to understand the impact of healthcare-associated infections in the intensive care unit and the bacterial resistance mechanisms involved. Methodology: This is a descriptive cross-sectional study with a retrospective design and case-control analysis, using data collected from the Hospital Infection Control Committee and electronic medical records of patients admitted to the intensive care unit of a tertiary university hospital in southern Brazil from January 2019 to December 2022. Results: The study analyzed 540 ICU patient records from 2019 to 2022, with 151 coinfected and 726 HAI cases. Most were male, with a median age of 61 years, and hypertension was the most common comorbidity. The most frequent infections were ventilator-associated pneumonia (32%) and tracheobronchitis (19%). Mortality increased from 34% (2019) to 51% (2022), and there was a rise in multidrug-resistant microorganisms, especially gram-negatives. Klebsiella pneumoniae (16%) and Acinetobacter baumannii (15%) were the most common microorganisms. Conclusion: Increased mortality and the higher occurrence of multidrug-resistant microorganisms were observed during this period. Additionally, there was a shift in the bacterial profile of these infections, now with a predominance of gram-negative microorganisms.